IL-2 and TCR stimulation induce expression and secretion of IL-32β by human T cells - Sanna, Franziska Christine; Benešová, Iva; Pervan, Philip; Krenz, Adriana; Wurzel, Alexander; Lohmayer, Robert; Mühlbauer, Jasmin; Wöllner, Amélie; Köhl, Nina; Menevse, Ayse Nur; Stamova, Slava; Volpin, Valentina; et al. (Frontiers in Immunology, 2024)
IL-32 expression is important for pathogen clearance but detrimental in chronic inflammation, autoimmunity, and cancer. T cells are major IL-32 producers in these diseases and key mediators of pathogen and tumor elimination but also autoimmune destruction. However, their contribution to IL-32 biology during immune responses is hardly understood due to several isoforms with divergent inflammatory properties. Here, we identified IL-32β as the predominant isoform in various T cell subsets of healthy individuals and breast cancer patients with the highest levels detected in intratumoral regulatory T cells. We show that IL-32β is induced by IL-2 but IL-32β release requires T Cell Receptor rather than IL2R stimulation. Using inhibitors of protein secretion pathways and serial (ultra)centrifugation of T cell supernatants, we demonstrate that T cells actively secrete IL-32β unconventionally, as a free protein and, to a minor degree, through exosomes. Thus, our data identify activated T cells as major IL-32β secretors in health and cancer.